PENGARUH PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2008 TENTANG PELAKSANAAN UJIAN AKHIR SEMESTER TERHADAP KOMPETENSI KARYAWAN PENGUJIAN DI UNIT PROGRAM BELAJAR JARAK JAUH UNIVERSITAS TERBUKA PEKANBARU - Utami, Tiwi Nurjannati (Jurnal Organisasi Dan Manajemen, 2011)
The Quality Management System Certificate ISO 9001:2008 awarded to UPBJJ-UT Pekanbaru indicated that it had used a variety of standard procedures in a variety of services area including the implementation of the final exam. This paper intends to investigate whether the implementation of ISO procedures affect the competence of examination staff UPBJJ-UT Pekanbaru. Regression analysis technique used to see the impact of implementation ISO procedures on staff competence. From this research we concluded that the implementation of ISO procedures do not affect the competency of staff because the ISO procedures are not adaptive to the condition of the field.